Discussion forum model in the Covid-19 pandemic era at Batu Api Library - Rachmawati, Tine Silvana (Jurnal Kajian Informasi dan Perpustakaan, 2023)
Discussion forums are activities to distribute information, ideas, and question. The Batu Api Library held discussion forums to exchange ideas that are discussed and presented through a problem or question that must be resolved based on a joint opinion or decision. This research aimed to find out the discussion forum model at the Batu Api Library during the pandemic with analysis discussion forum model and the development of library services through discussion forums. The research method used is a qualitative approach with a case study research method. The research was carried out for four months, from February to May 2022, using in-depth interview techniques with five people as the number of subjects in this study. The study results stated that during the pandemic, the Batu Api Library continued to conduct discussion forum activities, despite several changes due to the pandemic. Discussion forum at the Batu Api Library is sharing knowledge activity that source library collections. The discussion forum model in the pandemic era at Batu Api Library can be a bridge between users and the library. The discussion forum was also to develop library services so that more people would visit the library. In conclusion, the Batu Api Library can still conduct discussion forum activities as part of library services during the Covid-19 pandemic; this aligns with the statement that libraries are organisms that can constantly develop even during the Covid-19 pandemic.